Cytomegalovirus infection is associated with increased mortality in the older population. Issue 3 (19th April 2013) - Savva, George M.; Pachnio, Annette; Kaul, Baksho; Morgan, Kevin; Huppert, Felicia A.; Brayne, Carol; Moss, Paul A. H.; ,
Summary Cytomegalovirus (CMV) is a common herpesvirus infection and stimulates the expansion of very large numbers of CMV‐specific T cells that reduce the CD4/CD8 ratio and suppress the number of naïve T cells. CMV infection has been associated with frailty and impaired survival. We investigated the correlates of CMV and the impact of the CMV infection on mortality within a cohort of 511 individuals aged at least 65 years who were followed up for 18 years. The mean age of the participants was 74 years of which 70% were CMV‐seropositive. CMV was strongly linked to socio‐economic status, and CMV infection increased the annual mortality rate by 42% (Hazard ratio = 1.42, 95% CI: 1.11–1.76 after adjusting for age, sex and baseline socio‐economic and health variables) corresponding to 3.7 years lower life expectancy from age 65. Infection was associated with a near doubling of cardiovascular deaths, whereas there was no increase in mortality from other causes. These results show that CMV infection markedly increases the mortality rate in healthy older individuals due to an excess of vascular deaths. These findings may have significant implications for the study of immune senescence and if confirmed more generally could have important implications for measures to optimize the health of the elderly.